Rotavirus acute gastroenteritis among Filipino children - Daag, Jedas; Santos, Maria; Bravo, Lulu C; Ines, Bettina L
This is a prospective study to determine the clinical profile, of pediatric patients less than 5 years old with rotavirus diarrhea seen at the Philippine General Hospital from August 1-September 15, 2001. Ninety-one patients with acute diarrhea were included in the study. Of these 39 patients (42.9 percent) had rotavirus antigen in the stool as detected by the ELISA method. The mean age of the patients was 11.5 months with 61.5 percent of the patients belonging to the 7-12 months of age, mostly well-nourished. The stools were described as watery (74.4 percent), yellow in color (84.7 percent), with no pus, red blood cells or parasite. Average duration of diarrhea prior to consultation was 2.5 +/- 1.8 days with 7 episodes per day. Vomiting, fever and concomitant upper respiratory tract infection were noted in 76.9 percent, 64 percent and 23.7 percent of the patients respectively. A comparison of the rotavirus versus bacterial etiology of diarrhea showed fever and vomiting to be more predominant in rotavirus while dehydration was noted in bacterial isolates. Antibiotic was noted to be given to 38.5 percent rotavirus cases. Increased awareness of rotavirus diarrhea, regarding its high incidence and clinical profile, will help guide physicians in their rational use of antibiotics for patients with acute diarrhea. (Author)
In: Acta Medica Philippina, 2005 vol. 39 (1) pages: 36-42
Keywords: Rotavirus; Gastroenteritis; Child